Transcriptional characterization of human megakaryocyte polyploidization and lineage commitment. (29th March 2021) - Choudry, Fizzah A.; Bagger, Frederik O.; Macaulay, Iain C.; Farrow, Samantha; Burden, Frances; Kempster, Carly; McKinney, Harriet; Olsen, Lars R.; Huang, Ni; Downes, Kate; Voet, Thierry; Uppal, Rakesh; et al.
Abstract: Background: Megakaryocytes (MKs) originate from cells immuno‐phenotypically indistinguishable from hematopoietic stem cells (HSCs), bypassing intermediate progenitors. They mature within the adult bone marrow and release platelets into the circulation. Until now, there have been no transcriptional studies of primary human bone marrow MKs. Objectives: To characterize MKs and HSCs from human bone marrow using single‐cell RNA sequencing, to investigate MK lineage commitment, maturation steps, and thrombopoiesis. Results: We show that MKs at different levels of polyploidization exhibit distinct transcriptional states. Although high levels of platelet‐specific gene expression occur in the lower ploidy classes, as polyploidization increases, gene expression is redirected toward translation and posttranslational processing transcriptional programs, in preparation for thrombopoiesis. Our findings are in keeping with studies of MK ultrastructure and supersede evidence generated using in vitro cultured MKs. Additionally, by analyzing transcriptional signatures of a single HSC, we identify two MK‐biased HSC subpopulations exhibiting unique differentiation kinetics. We show that human bone marrow MKs originate from these HSC subpopulations, supporting the notion that they display priming for MK differentiation. Finally, to investigate transcriptional changes in MKs associated with stress thrombopoiesis, we analyzed bone marrow MKs from individuals with recent myocardial infarction and found a specific gene expression signature. Our data support the modulation of MK differentiation in this thrombotic state. Conclusions: Here, we use single‐cell sequencing for the first time to characterize the human bone marrow MK transcriptome at different levels of polyploidization and investigate their differentiation from the HSC.